Impact Analysis of Interface Thermal Conductivity on Pantograph-Catenary Contact Temperature Rise - BI Yonglei; WU Aizhong; SONG Enhao (Chengshi guidao jiaotong yanjiu)
［Objective］ The interface temperature rise caused by PC (pantograph-catenary) contact in electric trains can accelerate the wear of pantograph strips, thereby increasing the maintenance costs of rail transit systems. Therefore, studying the temperature rise in PC contact is of significant importance. ［Method］ Joule heating from contact resistance is one of the primary sources of temperature rise in PC contact, while the thermal conductivity characteristics of the contact interface influence the temperature distribution of the contact pair, both factors are critical to the temperature field. First, calculation models for PC contact resistance and thermal conductivity are derived. Then, a 3D finite element model of the strip and contact wire system is established for multi-physics coupling calculations to analyze the effect of the strip′s thermal conductivity rate on the contact thermal conductivity coefficient and temperature rise. ［Result & Conclusion］ Analysis results show that a heat ′accumulation′ phenomenon occus in the strip under prolonged contact condition; increasing the thermal conductivity of strips can reduce the contact temperature rise, thereby mitigating thermal damage to the strips.